PARP inhibitor era in ovarian cancer treatment: a systematic review and meta-analysis of randomized controlled trials - István Baradács; Brigitta Teutsch; Alex Váradi; Alexandra Bilá; Ádám Vincze; Péter Hegyi; Tamás Fazekas; Balázs Komoróczy; Péter Nyirády; Nándor Ács; Ferenc Bánhidy; Balázs Lintner (BMC, 2024)
Abstract Background Ovarian cancer is the eighth leading cause of cancer-related death among women, characterized by late diagnosis and a high relapse rate. In randomized controlled trials, we aimed to evaluate the efficacy and safety of PARP inhibitors (PARPi) in treating advanced ovarian cancer. Methods This review was registered on PROSPERO (CRD42021283150), included all phase II and phase III randomized controlled trials (RCTs) assessing the effect of PARPi on ovarian cancer until the 13th of April, 2022. The main outcomes were progression- free survival (PFS), overall survival (OS), and adverse events (AEs). Pooled hazard ratios (HRs), and risk ratios (RRs) were calculated with 95% confidence intervals (95% CI). The random-effects model was applied in all analyses. Results In the meta-analysis, 16 eligible RCTs were included, with a total of 5,815 patients. In recurrent ovarian cancer, PARPi maintenance therapy showed a significant PFS benefit over placebo in the total population (HR 0.34, CI 0.29-0.40), BRCA mutant (HR 0.24, CI 0.18-0.31), germline BRCA mutant (HR 0.23, CI 0.18-0.30), and BRCA wild-type cases (HR 0.50, CI 0.39-0.65). PARPi monotherapy also improved PFS (HR 0.62, CI 0.51-0.76) compared with chemotherapy in BRCAm patients with recurrent ovarian cancer. The use of PARPi maintenance therapy resulted in an improvement in PFS over placebo in newly-diagnosed cancers in the overall population (HR 0.46, CI 0.30-0.71) and the BRCAm population (HR 0.36, CI 0.29-0.44). Although the risk of severe AEs was increased by PARPi therapy compared to placebo in most settings investigated, these side effects were controllable with dose modification, and treatment discontinuation was required in the minority of cases. Conclusions PARPis are an effective therapeutic option for newly-diagnosed and recurrent ovarian cancer. Despite a minor increase in the frequency of serious adverse effects, they are generally well tolerated.